The Role of Electronic Auditing in Improving the Quality of External Auditing: Perspectives from a Sample of Professionals and Academics - meliani, wail; saoud, wassila (Journal of Research in Finance and Accounting, 2025)
The study aims to test the correlation between the use of e-auditing and the quality of external auditing, based on the analysis of responses from a sample of professionals (audit offices) and academics (university professors), totaling 35 individuals, using the SPSS program. The study found a significant-close correlation between the variables, where the utilization of e-auditing procedures improves the quality of external auditing; additionally, auditors adhere to their tasks and responsibilities in the context of e-auditing. The study recommends that guidelines and instructions should be drawn up by the accounting bodies that regulate the auditing profession to ensure that the task is performed in a quality manner, and that those workshops should be opened nationally to develop explicit laws, standards, and guidelines governing e-auditing in the Algerian environment.